Comparison of continuous and rotational grazing systems on veld condition, calving percentages and body condition of selected wildlife species - Somers, Michael J. (University of Pretoria, 2024)
Mini Dissertation (MSc (Wildlife Health, Ecology, and Management))--University of Pretoria, 2024.